2009
DOI: 10.1089/apc.2008.0008
|View full text |Cite
|
Sign up to set email alerts
|

HIV Care Providers' Implementation of Routine Alcohol Reduction Support for Their Patients

Abstract: Screening and brief intervention (SBI) for alcohol reduction is an important health promoting strategy for patients with HIV, and HIV care providers are optimally situated to support their patients' reduction efforts. We report results from analyses that use data collected from providers (n ¼ 115) in 7 hospital-based HIV care centers in the New York City metropolitan area in 2007 concerning their routine use of 11 alcohol SBI components with their patients. Providers routinely implemented 5 or more of these al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 51 publications
2
31
0
Order By: Relevance
“…Using a large variety of measures and definitions of unhealthy alcohol use, these studies have reported prevalences ranging from 8% on the low end (1) to approximately 42% on the high end (12, 14). Studies specifically using the AUDIT-C have identified prevalences ranging from 14% – 27% (8, 11, 13, 15, 33). The prevalence of unhealthy alcohol use identified using the AUDIT-C in the present study—22%—falls well within the range of previous estimates among PLWH and is similar to the general prevalence in the U.S. population (22.6%) (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a large variety of measures and definitions of unhealthy alcohol use, these studies have reported prevalences ranging from 8% on the low end (1) to approximately 42% on the high end (12, 14). Studies specifically using the AUDIT-C have identified prevalences ranging from 14% – 27% (8, 11, 13, 15, 33). The prevalence of unhealthy alcohol use identified using the AUDIT-C in the present study—22%—falls well within the range of previous estimates among PLWH and is similar to the general prevalence in the U.S. population (22.6%) (29).…”
Section: Discussionmentioning
confidence: 99%
“…The Alcohol Use Disorders Identification Test Consumption (AUDIT-C) questionnaire, which has been shown to perform well in persons with HIV (13), was administered to assess alcohol use. The AUDIT-C consists of three items that assess the quantity and frequency of average consumption and the frequency of heavy episodic drinking.…”
Section: Methodsmentioning
confidence: 99%
“…39 The findings of this study suggest that proactive screening and referral for counseling about alcohol use should be a component of HIV care in this regional setting, including support for provider-based training. 45 Participants with lower levels of general health perceptions and higher levels of distress were more likely to be nonadherent. Earlier studies from varying regional settings have identified psychological distress as a barrier to optimal adherence.…”
Section: Venkatesh Et Almentioning
confidence: 97%
“…Recent work suggests that patients with HIV have common beliefs that drinking alcohol is toxic when taking ART and as a result stop taking ART when drinking, which may lead to general ART nonadherence [56]. Other work highlights the significance of educating providers about the negative effects of alcohol and the importance of disconfirming beliefs and myths about the toxicity of alcohol use and ART [57].…”
Section: Alcoholmentioning
confidence: 99%